Políticas públicas de desenvolvimento no território do Alto Sertão Sergipano : entre a governança e a sustentabilidade - Santos, Carmem Lúcia (2014)
Social vulnerability and poverty, present mainly in the Brazilian rural areas, originated from a style of development characterized by clearly biased urban concepts of land and income concentration have made family reproduction difficult, besides stimulating rural exodus. Such scenario has made the government rethink its rural development policies by adopting a territorial approach seen as a mechanism of social inclusion, i.e., more participative and better adapted to the local reality. However, the efficacy of the public territorial policies has been questioned, motivating us to carry out this work. The general objective is to analyze the territorial development policies under the perspective of governance and sustainability, as represented by the counselors of Territory of Alto Sertão Sergipano (TASS) and the families benefited by the Sustainable Rural Territorial Development Plan (PDTRS). Answers were sought to the following questions: Are the TASS development policies conceived as sustainable by the actors involved in function of their social representations? Have the governance practices turned into collective projects and environments for participation, thus contributing to a sustainable territorial development? Has the qualitative-quantitative survey applied the theory of social representations regarding the counselors and the benefited families, as well as regarding data collection tools such as bibliographic review, census and document registration, semi-structured interviews, life history, participative observation, and photographic records of everyday life? The results showed that there is a coherent link between the social representations of the participants regarding territorial sustainability and public policies and the empirical theoretical- conceptual basis. It was concluded that the governance of the TASS development policies, based onasymmetric relations and decision making processes has not favored the collective projects, being limited by their institutional fragility and distorted territorial views. Social cohesion should be increased and the mechanisms of identity and solidarity should be strengthened in the territory by means of a new organizational culture favoring public territorial policy sustainability.